On the use of glutamine-containing specialty foods in sports - A. V. Slivin; P. V. Efimov; A. V. Zorenko; M. V. Kupeev; T. A. Yashin; M. Y. Yadgarov; S. A. Bazanovich; N. S. Philippova; S. A. Parastaev (National Electronic Information Consortium (NEICON), 2022)
Glutamine (GLN) and glutamic acid (GLA) are involved in many metabolic processes, from nucleotide synthesis to nerve impulse conduction; GLN is also an energy substrate for immunocompetent cells, making it an important link in the immune response. In stressful situations, which include significant physical activity, plasma levels of GLN and GLA decrease as a result of the amino acid being actively consumed in many biochemical reactions. GLN deficiency can lead to a number of negative manifestations in athletes and adversely affect athletic performance. The purpose of this work was to study the effects of glutamine deficiency and the possible replenishment of the deficiency by the consumption of exogenous forms of the substance when using glutamine-containing products; special attention was paid to the study of transient decrease in immune function as a relevant factor that impairs the mode of sports training.